2024
DOI: 10.1186/s40510-023-00503-1
|View full text |Cite|
|
Sign up to set email alerts
|

Curve of Spee modification in different vertical skeletal patterns after clear aligner therapy: a 3D set-up retrospective study

Domenico Ciavarella,
Carlotta Fanelli,
Carmela Suriano
et al.

Abstract: Objective The purpose of the present study was to evaluate: (1) changes in the curve of Spee (COS) after clear aligner therapy and (2) whether such changes correlated with the patient’s skeletal patterns. Materials and methods Three-dimensional mandibular models of 106 patients (47 males and 59 females; mean age 22.3 SD ± 3.4 years) treated with clear aligners were retrospectively analysed. The perpendicular distance between the occlusal reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, several studies [ 11 – 13 ] have highlighted the impact of material hardness on clear aligners. They have found that these aligners often fail to maintain their original shape when closing gaps, leading to mesiodistal tilting of molars and the loss of buccolingual torque [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several studies [ 11 – 13 ] have highlighted the impact of material hardness on clear aligners. They have found that these aligners often fail to maintain their original shape when closing gaps, leading to mesiodistal tilting of molars and the loss of buccolingual torque [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%